2013
DOI: 10.1002/hep.26547
|View full text |Cite
|
Sign up to set email alerts
|

Receptor interacting protein kinase 3 is a critical early mediator of acetaminophen-induced hepatocyte necrosis in mice

Abstract: Acetaminophen (APAP) overdose is a major cause of hepatotoxicity and acute liver failure in the US, but the pathophysiology is incompletely understood. Despite evidence for apoptotic signaling, hepatic cell death after APAP is generally considered necrotic in mice and in humans. Recent findings suggest that the receptor interacting protein kinase 3 (RIP3) acts as a switch from apoptosis to necrosis (programmed necrosis). Thus, the aim of the current investigation was to determine if RIP3 is involved in APAP-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
247
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 230 publications
(266 citation statements)
references
References 43 publications
11
247
3
Order By: Relevance
“…However, the role of programmed hepatocellular death in acetaminophen-induced (APAP-induced) murine liver damage remains controversial. Although inhibition of necroptosis by deficiency of RIPK3 (17) or pharmacological blockage of RIPK1 kinase activity (18) reduced cell death at early time points during APAP-induced hepatic injury, RIPK3 and MLKL deficiency was unable to prevent liver injury in this model (19). Other studies further demonstrated that ethanol-induced hepatic injury is independent of RIPK1 kinase activity but dependent on RIPK3, suggesting that necroptosis does not always require RIPK1 function (20).…”
Section: Introductionmentioning
confidence: 90%
“…However, the role of programmed hepatocellular death in acetaminophen-induced (APAP-induced) murine liver damage remains controversial. Although inhibition of necroptosis by deficiency of RIPK3 (17) or pharmacological blockage of RIPK1 kinase activity (18) reduced cell death at early time points during APAP-induced hepatic injury, RIPK3 and MLKL deficiency was unable to prevent liver injury in this model (19). Other studies further demonstrated that ethanol-induced hepatic injury is independent of RIPK1 kinase activity but dependent on RIPK3, suggesting that necroptosis does not always require RIPK1 function (20).…”
Section: Introductionmentioning
confidence: 90%
“…RIP3 À/À mice were generously provided by Dr. Vishva Dixit (Genentech, San Francisco, CA) as we described previously. 18 All mice were housed in cages (five mice per cage) receiving a 12-hour light/dark cycle. Mice were injected intraperitoneally with 100 mg/kg LPS and 700 mg/kg GalN for 6 hours.…”
Section: Animalsmentioning
confidence: 99%
“…Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining was performed as described previously. 18 …”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Much effort has been invested to gain a better understanding of the molecular mechanisms of APAP hepatotoxicity (Saito et al 2010;Kon et al 2004;Hwang et al 2015;Sjogren et al 2014;Schyschka et al 2013;Singh et al 2013) and to identify biomarkers of APAP overdose (McGill et al 2014;Beger et al 2015). APAP is known to be metabolically activated to the reactive N-acetyl-p-benzoquinone imine (NAPQI), which forms protein adducts including mitochondrial proteins leading to mitochondrial oxidative stress (Ramachandran et al 2013;Cohen et al 1997). As a consequence c-jun N-terminal kinase is translocated to the mitochondria, which enhances generation of reactive oxygen species (Ramachandran et al 2013;Hanawa et al 2008;Saito et al 2010).…”
mentioning
confidence: 99%
“…APAP is known to be metabolically activated to the reactive N-acetyl-p-benzoquinone imine (NAPQI), which forms protein adducts including mitochondrial proteins leading to mitochondrial oxidative stress (Ramachandran et al 2013;Cohen et al 1997). As a consequence c-jun N-terminal kinase is translocated to the mitochondria, which enhances generation of reactive oxygen species (Ramachandran et al 2013;Hanawa et al 2008;Saito et al 2010). This may lead to opening of the mitochondrial membrane transition pore and cause a form of cell death which differs from classical apoptosis and has been named 'necroptosis' (Kon et al 2004;Gujral et al 2002;Ni et al 2012).…”
mentioning
confidence: 99%